2019
DOI: 10.3390/chemosensors8010002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ZnO Flakes on Flexible Substrate and Its Application on Ethylene Sensing at Room Temperature

Abstract: As a hormone that determinates the level of fruit ripeness, ethylene concentration monitoring plays an important role in the agricultural field. One of the techniques that can be used to detect ethylene concentration is the sensing method. Zinc oxide (ZnO) is a multipurpose metal oxide semiconductor with a wide application in sensing area. Here, we use a ZnO-based flexible sensor to identify the presence of ethylene gas at certain concentrations. The as-synthesized ZnO layers were deposited on a polyethylene t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…When considering the possible mechanism of the influence of nickel on the sensory properties of the Ni/rGO/WO 3 composite, in addition to selective catalytic activity, it is also possible to refer to the existing explanation for the interaction of clusters of metal particles with a semiconductor. In accordance with the literature data, the role of nickel in increasing the sensory sensitivity is most likely associated with the spillover effect [60,61]. When interacting with a gas atom, the barrier height at the Ni/rGO interface decreases due to this effect (the possibility of electron transfer from nickel particles to rGO and WO 3 ), which leads to a greater decrease in the resistance of the composite.…”
Section: Gas Sensing Measurements On Gas Permeable Pelletssupporting
confidence: 86%
“…When considering the possible mechanism of the influence of nickel on the sensory properties of the Ni/rGO/WO 3 composite, in addition to selective catalytic activity, it is also possible to refer to the existing explanation for the interaction of clusters of metal particles with a semiconductor. In accordance with the literature data, the role of nickel in increasing the sensory sensitivity is most likely associated with the spillover effect [60,61]. When interacting with a gas atom, the barrier height at the Ni/rGO interface decreases due to this effect (the possibility of electron transfer from nickel particles to rGO and WO 3 ), which leads to a greater decrease in the resistance of the composite.…”
Section: Gas Sensing Measurements On Gas Permeable Pelletssupporting
confidence: 86%
“…This improvement is due to the phenomenon of surface plasmon resonance (SPR) on the sensor surface. The SPR phenomenon enhances the O 2 absorption process on the surface and eventually helps to achieve fast response and recovery times [52]. This scheme of enhanced performance has been depicted in Fig.…”
Section: Literature Surveymentioning
confidence: 96%
“…Their work reported gas sensing at 15 ppm level [51]. ZnO in the form of nanofiber (1D) [57], nanosheet (2D) [58,59], and microspheres (3D) [60,61] have been also reported as sensing elements for detecting gases. For instance, Du et al [57] reported 1D ZnO nanofiber for sensing acetone with a sensitivity of 125Ra/Rg and a response time of 75 s@100 ppm.…”
Section: Literature Surveymentioning
confidence: 99%
“…In optoelectronics, various ZnO nanostructures are used for producing e.g., refractive index sensors [ 123 ], surface-enhanced Raman scattering (SERS) sensors [ 124 ], lasers, UV detectors, and UV diodes [ 74 , 125 , 126 , 127 , 128 ]. ZnO nanostructures may serve for producing sensors of gases [ 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 ] such as steam (humidity, H 2 O) [ 133 ], ammonia (NH 3 ) [ 129 , 130 , 131 , 143 ], nitrogen (N 2 ) [ 131 ], nitrogen monoxide (NO) [ 129 , 130 , 139 ], nitrogen dioxide (NO 2 ) [ 129 , 131 , 134 , 135 , 136 ,…”
Section: Introductionmentioning
confidence: 99%